2019
DOI: 10.4468/2019.2.05dandrea.pizzichini.marasca.gregori
|View full text |Cite
|
Sign up to set email alerts
|

CSR Communication: The Use of Internet-Based Tools

Abstract: Corporate communication plays an important role in establishing and maintaining transparent and open dialogues with different stakeholders to foster ethical and socially responsible actions. The advent of the internet not only reorganized the way in which companies collect information, but also redefined stakeholders' expectations. This paper investigates the potential of internet-based communication tools to disclose CSR topics. The study analyses the extent to which the Dow Jones Sustainability Index compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…An uncertain scenario like a pandemic offers exciting information to understand the changed need of people who use online channels as the primary way to shop. In fact, the digital communication channels will also become a priority for companies for the rapid transfer from offline to online media (D'Andrea et al. , 2019).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…An uncertain scenario like a pandemic offers exciting information to understand the changed need of people who use online channels as the primary way to shop. In fact, the digital communication channels will also become a priority for companies for the rapid transfer from offline to online media (D'Andrea et al. , 2019).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The exponential growth of social media (SM) has evolved in a transformation in the communication environment in which stakeholders as users are able to publish and share their opinions about businesses and their products ( D’Andrea et al, 2019 ). This is a particularly important activity as recent studies have shown the benefits of CSR communication with stakeholders ( Bartikowski & Berens, 2021 ; Husnaini, Sasanti & Cahyaningtyas, 2018 ; Viererbl & Koch, 2022 ; Withisuphakorn, 2018 ).…”
Section: Introductionmentioning
confidence: 99%